Adoption and impact of improved wheat varieties on productivity and welfare among smallholder farmers in the Arsi Highland of Ethiopia. Issue 2 (3rd April 2022) - Zeleke, Bedilu Demissie; Geleto, Adem Kedir; Asefa, Sisay; Komicha, Hussien H.
ABSTRACT: This article evaluates the adoption and impact of improved wheat varieties on rural farm household welfare measured by consumption expenditure per adult equivalent and productivity per hectare in rural Ethiopia. The study utilises cross-sectional farm household-level data collected in 2017/2018 from a randomly selected sample of 323 farmers in Arsi Highland of Ethiopia. We estimate the adoption and causal impact of improved varieties by utilising endogenous switching regression complemented with a binary propensity score matching methodology. This helps us estimate the productivity and welfare effect of technological adoption by controlling for the role of selection bias problem stemming from both observed and unobserved heterogeneity. Our analysis reveals a consistent result across models indicating that adoption enhances wheat productivity per hectare by 0.63 tons/ha and household welfare by 31%. Even farm households that did not adopt would benefit significantly had they adopted. Education, wheat price, farm machineries, crop rotation, row planting, social capital (such as informal network, core trust, and institutional trust), training on varieties selection, and information on seed availability are found to be the main drivers behind the adoption of improved wheat varieties.